Upper versus Lower Lumbar Lordosis Corrections in Relation to Pelvic Tilt – An Essential Element in Surgical Planning for Sagittal Plane Deformity. Issue 16 (15th August 2022) - Kim, Han Jo; Alluri, R. Kiran; Lafage, Renaud; Elysee, Jonathan; Smith, Justin S.; Mundis, Gregory M.; Shaffrey, Christopher I.; Ames, Christopher P.; Burton, Douglas C.; Klineberg, Eric O.; Bess, Shay; Schwab, Frank; et al.
Abstract : Study Design: Retrospective study of a multicenter Adult Spinal Deformity (ASD) Database. Objective: To investigate the change in Pelvic tilt (PT) imparted by regional changes in lumbar lordosis at 2-year minimum follow up Summary of Background Data: The distribution of lumbar lordosis between L1-4 and L4-S1 is known to vary based on pelvic incidence (PI). However, the extent to which regional changes effect PT is not clearly elucidated. This information can be useful for ASD surgical planning. Methods: Operative patients from a multicenter ASD database were included with Lowest Instrumented Vertebrae (LIV) S1/Ilium, >5 levels of fusion, Proximal Junction Kyphosis (PJK) angle < 20, and >5 degrees of change in lumbar lordosis from L4-S1 and L1-4. Radiographic analysis was performed evaluating Thoracic Kyphosis (TK), T10-L2 kyphosis (TL), L1-S1 lordosis (LL), L4-S1 lordosis, L1-4 lordosis, sagittal vertical axis (SVA) and PI-LL from preoperative to postoperative, and change at 2-years follow-up. Stepwise regression analysis was performed in order to determine the relationship between PT and the above radiographic parameters. Health-related quality of life (HRQOL) outcomes were also compared between preoperative and postoperative timepoints at 2 years. Results: 103 patients met inclusion for the study. There was improvement in all the radiographic parameters and HRQOLs at 2 years follow-up (p < 0.01). Stepwise regression model showed an inverse relationship between PT and LL change (r = 0.71, p < 0.01). Regionally, an increase in 10 degrees from L4-S1 correlated with a 2.4 degree decrease in PT (p < 0.01), while an increase in 10 degrees from L1-4 resulted in a 1.6 degree decrease in PT (p < 0.01). Conclusion: In the surgical planning for ASD, our data demonstrated significant correlational difference between corrections in the upper (L1-4) and lower (L4-S1) lumbar spine and PT changes. These calculations can be useful in planning sagittal plane corrections for ASD.